THE INFLUENCE OF SUPERVISION AND WORK COMPETENCY ON THE WORK EFFECTIVENESS OF THE EMPLOYEES OF THE BUREAU OF WAREHOUSE RECEIPT SYSTEM AND COMMODITY AUCTION MARKET DEVELOPMENT AND DEVELOPMENT OF BAPPEBTI, MINISTRY OF TRADE - Maulida Afiaty; Enjang Sudarman; Bambang Nurakhim (Yayasan Pendidikan Cahaya Budaya Indonesia, 2026)
This study aims to determine the effect of supervision and work competence on the work effectiveness of employees of the warehouse receipt system and commodity auction market development bureau of the Ministry of Trade. The phenomenon underlying this study is the discovery of employees with a suboptimal level of work effectiveness. In this study the author used quantitative research. The population in this study was 145 employees. In this study the author used a sampling technique using the Slovin formula of 59 people. Data were collected using a closed questionnaire with a Likert scale, and analyzed using multiple linear regression with the help of the SPSS program version 20. The results of the study indicate that partially and simultaneously, the influence of supervision and work competence has a positive and significant effect on work effectiveness. This study emphasizes the importance of being able to follow up with appropriate policies in order to be able to increase work effectiveness optimally.